2001
DOI: 10.1177/00912700122010384
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Dose Gabapentin Pharmacokinetics and Safety in Healthy Infants and Children

Abstract: Gabapentin (Neurontin) is a gamma-aminobutyric acid analogue indicated in adults for adjunctive treatment of partial seizures with or without secondary generalization. Two studies were conducted to determine the single-dose pharmacokinetics of gabapentin in healthy subjects age 1 month to 12 years and to guide dose selection in safety and efficacy trials in pediatric patients. Forty-eight subjects were given single oral doses of gabapentin (10 mg/kg) while fasting. Enrollment was homogeneously distributed thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 18 publications
1
33
3
Order By: Relevance
“…[1][2][3] Gabapentin was used in this cohort given its safety and reported use in children with SNI. [6][7][8] The purpose of this retrospective analysis is to better understand gabapentin use in a larger cohort of individuals with SNI and recurrent pain behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Gabapentin was used in this cohort given its safety and reported use in children with SNI. [6][7][8] The purpose of this retrospective analysis is to better understand gabapentin use in a larger cohort of individuals with SNI and recurrent pain behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Still on its effects, GABA has also been linked to the effectiveness of cascade action processes. Consistent with this hypothesis, Yildiz et al (2014) have shown by magnetic resonance spectroscopy (MRS) that superior performance of cascade action was associated with increased striatal GABA concentrations [98]. Another point, the active transcutaneous stimulation of the vagus nerve (tVNS) which increases the concentration of GABA and norepinephrine (NE), improved functions of response selection during the cascade action, compared with the stimulus simulation [99].…”
Section: Gabamentioning
confidence: 96%
“…These results suggest a critical role of GABA in the neuromodulation of cascade action processes. They also suggest that the increase [98,99] not too high [100] of GABA levels are associated with better performance of these cascade actions. In another study, Steenbergen et al (2015b) aimed to provide converged and direct evidence about the possible key role of the GABAergic system in modulating the efficacy of cascade action [101].…”
Section: Gabamentioning
confidence: 97%
“…However, gabapentin does not bind adjunct therapy in 247 pediatric patients with refractory partial to GABA receptors, mimic GABA, or affect GABA uptake. [84] seizures. [9] This study had a 6-week baseline period with a Currently, more is being discovered about the mechanism of 12-week double-blind phase.…”
Section: Pharmacology 32 Efficacymentioning
confidence: 99%